The Prevalence of Atopic Dermatitis and Chronic Spontaneous Urticaria are Associated with Parental Socioeconomic Status in Adolescents in China - Yi Xiao; Xiaoyan Huang; Danrong Jing; Yuzhou Huang; Liping Chen; Xingyu Zhang; Shuang Zhao; Mi Zhang; Zhongling Luo; Juan Su; Yehong Kuang; Jie Li; et al. (Medical Journals Sweden, 2018)
The association of atopic dermatitis and chronic spontaneous urticaria with socioeconomic status has been little studied. The aim of this study was to investigate the prevalence of skin diseases and their association with socioeconomic status in adolescents in China. A cross-sectional study was conducted at Central South University, Changsha, China. All newly enrolled students underwent dermatological examination and completed a survey. Socioeconomic status was measured in terms of parental education level and income. Two-level logistic regression models were used. A total of 8,226 students consented to participate. On dermatological examination, moderate to severe acne (10.2%) had the highest prevalence, followed by chronic spontaneous urticaria (2.7%), atopic dermatitis (2.5%), and tinea (1.7%). Socioeconomic status was positively associated with the prevalence of chronic spontaneous urticaria (ptrend = 0.001) and atopic dermatitis (ptrend = 0.0094). Tinea was inversely associated with socioeconomic status (ptrend = 0.025). Higher parental socioeconomic status was associated with higher risk of atopic dermatitis and chronic spontaneous urticaria, but lower risk of tinea.